PENGARUH MANAJEMEN LABA DAN TRANSFER PRICING TERHADAP PENGHINDARAN PAJAK - Suparna Wijaya; Hanafi Hidayat (Bina Ekonomi, 2021)
The tax avoidance practices by companies in Indonesia causes tax revenue targets to be difficult to achieve. This study aims to determine the effect of earning management and transfer pricing on the tax avoidance. The object of research is agricultural sector companies listed on Indonesia Stock Exchange in the 2016-2020 period. The data used is secondary data consisting of 35 financial reports picked using purposive sampling as sample selection method. Data analysis was performed using Common Effect Model-GLS Weights. The test results show that accrual earning management has no significant effect on tax avoidance, real earning management through operating cash-flow and real earning management through overproduction has significant negative effect on tax avoidance. However, real earning management through discretionary expense and transfer pricing has significant positive effect on tax avoidance. Keywords: tax avoidance, earning management, transfer pricing